2016
DOI: 10.1126/science.aad7977
|View full text |Cite
|
Sign up to set email alerts
|

Sperm tsRNAs contribute to intergenerational inheritance of an acquired metabolic disorder

Abstract: Increasing evidence indicates that metabolic disorders in offspring can result from the father's diet, but the mechanism remains unclear. In a paternal mouse model given a high-fat diet (HFD), we showed that a subset of sperm transfer RNA-derived small RNAs (tsRNAs), mainly from 5' transfer RNA halves and ranging in size from 30 to 34 nucleotides, exhibited changes in expression profiles and RNA modifications. Injection of sperm tsRNA fractions from HFD males into normal zygotes generated metabolic disorders i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
1,269
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,150 publications
(1,370 citation statements)
references
References 41 publications
(54 reference statements)
44
1,269
2
4
Order By: Relevance
“…The paternal preconception environment modulates the RNA content of the developing sperm, with possible effects on post-fertilization development and offspring phenotypes 53 . In animal studies, paternal exposures to high-fat and high-sugar diets produce metabolic disturbances in offspring 54 , and both stress and exercise affect stress responses of the offspring [55][56][57] . Animal and some human studies have found effects of preconceptional tobacco, alcohol and illicit drug use on gamete epigenomes, with diverse effects on offspring development 58,59 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…The paternal preconception environment modulates the RNA content of the developing sperm, with possible effects on post-fertilization development and offspring phenotypes 53 . In animal studies, paternal exposures to high-fat and high-sugar diets produce metabolic disturbances in offspring 54 , and both stress and exercise affect stress responses of the offspring [55][56][57] . Animal and some human studies have found effects of preconceptional tobacco, alcohol and illicit drug use on gamete epigenomes, with diverse effects on offspring development 58,59 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…This conclusion might be of particular relevance to human pathophysiology, since a recent study observed alterations in germline non-coding RNA of obese men [13]. Interestingly, data from zygotic injection experiments of synthetic tRNA fragments lacking post transcriptional modifications suggest that these modifications are indispensible to induce transgeneratioanal effects [11] while Sharma's study [7] suggests functionality of unmodified tRNA fragments. It remains to be seen how tsRNAs might act in embryos to relay information to the next generation.…”
mentioning
confidence: 65%
“…Alternatively, intergenerational effects could result if RNAs carry sequence-specific information to gametes through circulation from distant tissues that experience chemicals, changes in diet, or stress. In support of this possibility, studies focused on intergenerational and transgenerational effects in mammals implicate RNA in the inheritance of gene expression states across generations (47), report changes in small RNAs in gametes (48,49), and report changes in RNAs acquired during gamete maturation from surrounding epithelia (50,51). However, in all these cases, direct effects of a treatment-e.g., diet-on gametes and surrounding support tissues that alter RNA composition in gametes have not been ruled out.…”
Section: Rnas In Circulation As Carriers Of Gene-specific Informationmentioning
confidence: 99%